Complexity evaluation in scalable video coding - Maarif, Haris Al Qodri; Gunawan, Teddy Surya; Priantoro, Akhmad Unggul (CSC Publishers, 2010)
The scalable video coding is the extension of H.264/AVC. The features in scalable video coding, are the standard features in H.264/AVC and some features which is supporting the scalability of the encoder. Those features add more complexity in SVC encoder. In this paper, complexity evaluation of scalable video coding has been performed. Different scalable configurations were evaluated in which the encoding time and the encoded video quality have been measured. Various scalable configurations with various GOPs, frame rates, QP value, have been implemented and evaluated, which shows the scalability of video coding for various conditions. Based on these results, a low complexity algorithm has been proposed. Results show that the proposed algorithm maintained the image quality (around 0.1 dB differences) while reducing the encoding time (around 30%).